2014
DOI: 10.1073/pnas.1324140111
|View full text |Cite
|
Sign up to set email alerts
|

Role of caspase-1 in nuclear translocation of IL-37, release of the cytokine, and IL-37 inhibition of innate immune responses

Abstract: IL-37 is a fundamental inhibitor of innate immunity. Human IL-37 has a caspase-1 cleavage site and translocates to the nucleus upon LPS stimulation. Here, we investigated whether caspase-1 processing affects IL-37-mediated suppression of LPS-induced cytokines and the release from cells by analyzing a caspase-1 cleavage site mutant IL-37 (IL-37D20A). Nuclear translocation of IL-37D20A is significantly impaired compared with WT IL-37 in transfected cells. LPS-induced IL-6 was decreased in cells expressing WT IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
242
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(256 citation statements)
references
References 28 publications
9
242
1
4
Order By: Relevance
“…However, in the presence of a caspase-1 inhibitor, there is no translocation to the nucleus and no reduction in LPS-induced cytokines (7). Mutation of aspartic acid at the caspase-1 cleavage position 20 to alanine also results in failure to translocate to the nucleus and loss of the suppression of cytokine production (8). Thus, as with IL-1α and IL-33, IL-37 is the third member of the IL-1 family that translocates to the nucleus and affects cellular responses.…”
mentioning
confidence: 99%
“…However, in the presence of a caspase-1 inhibitor, there is no translocation to the nucleus and no reduction in LPS-induced cytokines (7). Mutation of aspartic acid at the caspase-1 cleavage position 20 to alanine also results in failure to translocate to the nucleus and loss of the suppression of cytokine production (8). Thus, as with IL-1α and IL-33, IL-37 is the third member of the IL-1 family that translocates to the nucleus and affects cellular responses.…”
mentioning
confidence: 99%
“…Therefore, we propose that the biological functions of IL37 variants need to be verified and compared with earlier experimental results using NCBI reference protein. 4,8,22 Second, our data provides valuable guidance on picking SNPs for disease association studies. Previous reports suggested that IL37 was involved in the development of various inflammatory conditions, including ankylosing spondylitis and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The IL37b is a precursor, which is thought to be processed by caspase-1 into the mature form and translocates actively into the cell nucleus. 4 IL37b mRNA has been found in multiple human tissues, including the lymph node, thymus, bone marrow, placenta, lung and testis. 5 IL37 protein level in PBMCs and dendritic cells is upregulated when stimulated by TLR ligands or proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that IL-37 is capable of inhibiting proinflammatory effects that are mediated through activation of receptors belonging to the interleukin-1 receptor/toll-like receptor (TIR) superfamily like TIRs 2 and 4 and the IL-1 receptor [30,31]. As shown in in vitro and in a wide range of animal models for chronic inflammatory diseases, this inhibition on the one hand results in further diminished production of proinflammatory cytokines such as IL-1α, IL-1β, IL-6, IL-17, IL-23, GM-CSF, and TNF-α and chemokines like CCL12, CXCL1, CXCL2, CXCL8, and CXCL13 [32][33][34]. On the other hand, IL-37 has been described to support IL-10 production, tolerogenic dendritic cell, and regulatory T cell activity [34,35].…”
mentioning
confidence: 97%
“…On the other hand, IL-37 has been described to support IL-10 production, tolerogenic dendritic cell, and regulatory T cell activity [34,35]. So far, its mode of action includes interference with the inflammasome, an intracellular activity as well as extracellular binding to IL-18 receptor α and the regulatory orphan receptor SIGIRR/IL-1R8 [31,32,36,37]. All these observations suggested that IL-37 could be a potent regulator of local innate immunity.…”
mentioning
confidence: 99%